Intelectuais, literatura e imprensa no pós-golpe - Czajka, Rodrigo [UNESP] (UNISINOS - Universidade do Vale do Rio Dos Sinos, 2014)
Culture and the arts in Brazil were impacted directly by the military coup from 1964 onwards. In spite of repression and censorship, the activity of intellectuals and artists in the pre-1964 period was not interrupted nor became stagnant, but gained even greater force due to the presence of control and restrictions by the institutions of repression over against the freedom of creation and thought. As in many sectors of cultural production, literature played a vigorously combative role against the arbitrariness of the regime and implemented projects of resistance on the basis of key elements of representation. This occurred, for instance, through the writing and circulation of works such as Pessach: a travessia, by journalist Carlos Heitor Cony, and Quarup, by journalist Antonio Callado. The two novels enabled a broad debate on the narrative form and the scope of involvement in the literature of the 1960s, such as the confrontation between Paulo Francis and Ferreira Gullar in the pages of Revista Civilização Brasileira, which is the focus of this article.
Intellectuals, literature and press in post-coup period
Keywords: Intellectuals; Involvement; Left; Literature; Military dictatorship; Press